Uma experiência de inserção de Linguagem de Programação no Ensino Médio Integrado à Educação Profissional Técnica a partir da flexibilização curricular - Fria, Bruno Lopes de (2021)
The principle of curricular flexibility presupposes innovations in the pedagogical projects of the courses to meet the new social realities, among which we highlight the contemporary technological immersion. In this sense, wepresent a curricular menu as a theoretical-methodological contribution to the development of skills related to the learning of a Programming Language (ie algorithmic thinking and problem solving in the real world in computational language) as a curricularunit applied to different professionais profiles at the level medium. The menu was consolidated through a holistic approach based on criteria such as coherence, feasibility and a learning curve that provide a global character due to the heterogeneity of training. The feasibility of the proposal was suggested by scale acceptance forms and observations made in the classroom context in the IFNMG/Diamantina integrated courses in Informatics, Environment and Theater. The students' level of learning was rated ona scale of 1 = very easy to 5 = very difficult, where we obtained an average of 2.57. The results indicate that in the adopted language, Python, no item was considered particularly difficult, which can be related to its compact and clean syntax, when compared to other programming languages. The preliminary application of the proposal at the IFNMG demonstrated good interaction between students and Python, as well as assimilation and the ability to reframe the acquired content through the construction of proposals for joint work and professional application.